A UNIQUE, PRICELESS MEMORIAL OF OUR PEOPLE - Hayitov Shavkat Ahmadovich; Bafoeva Maftuna Botir kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article deals with one of the most favourite writers and scientist of Uzbek literature Boqijon Tokhliev. His study on “Devonu Lug’otit Turk” and its analysis has been done in the article.